2013
DOI: 10.2967/jnumed.112.108233
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Visualization and Quantification of (Disturbed) Oatp-Mediated Hepatic Uptake and Mrp2-Mediated Biliary Excretion of 99mTc-Mebrofenin in Mice

Abstract: Hepatic transport of 99m Tc-mebrofenin through organic anion transport protein 1a and 1b (Oatp1a/1b) and multidrug resistance protein 2 (Mrp2) was investigated by small-animal SPECT. On the basis of the results, a noninvasive method to visualize and quantify disturbances in hepatic transport is proposed. Methods: Friend virus B wild-type mice (untreated, bile ductligated, vehicle-or rifampicin-treated) and strain-matched knockout mice unable to express the uptake transporters Oatp1a/1b (Slco1a/1b 2/2 / 2/2 ) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 23 publications
2
34
0
Order By: Relevance
“…The cellular mechanisms of cholestasis associate interactions with drug uptake in mice (van de Steeg et al, 2010;Neyt et al, 2013) as well as decrease bile excretion through Mrp2 in mice (Neyt et al, 2013) and human bile salt export pump in transfected cells (Mita et al, 2006). However, RIF has also beneficial effects in cholestatic liver diseases; chronic treatment with RIF enhances bile acid detoxification, bilirubin conjugation, and excretion in association with an increased hepatic expression of CYP3A4, UGT1A1, and MRP2 (Marschall et al, 2005).…”
Section: Drug-drug Interactions Within Hepatocytes 1553mentioning
confidence: 99%
“…The cellular mechanisms of cholestasis associate interactions with drug uptake in mice (van de Steeg et al, 2010;Neyt et al, 2013) as well as decrease bile excretion through Mrp2 in mice (Neyt et al, 2013) and human bile salt export pump in transfected cells (Mita et al, 2006). However, RIF has also beneficial effects in cholestatic liver diseases; chronic treatment with RIF enhances bile acid detoxification, bilirubin conjugation, and excretion in association with an increased hepatic expression of CYP3A4, UGT1A1, and MRP2 (Marschall et al, 2005).…”
Section: Drug-drug Interactions Within Hepatocytes 1553mentioning
confidence: 99%
“…The delay in hepatic uptake in NDEA animals may be due to severe hepatocellular dysfunction. Neyt et al [34] have also reported the delayed uptake due to the dysfunction of various Oatp transporters located on hepatocytes. The retention of radiotracer activity in the liver of NDEA mice up to 60 min showed marked impairment in the excretion of the activity.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, erythromycin treatment has no effect on clinical liver MRI with EOB-DTPA, but no other potentially competing drugs were investigated (Huppertz et al, 2011). In rodents, rifampicin administration blocks the rMRP2 and increases the hepatic accumulation of the SPECT tracer 99m Tc-mebrofenin (Neyt et al, 2013) and the PET tracers 11 C-telmisartan (Takashima et al, 2011) and [11C] TIC-Me (Kusuhara, 2013). Interaction of ritonavir with 99m Tc-mebrofenin was also recently investigated (Pfeifer et al, 2013).…”
Section: Modifications Of Transport Induced By Drug-drug Interactionsmentioning
confidence: 99%